2020
DOI: 10.11603/mcch.2410-681x.2020.v.i1.10936
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemic and Hypolipidemic Activity of Arginine Containing Bearberry Leaves Extract in Insulin Resistant Rats

Abstract: Introduction. In recent decades, diabetes mellitus type 2 (DM2) has become one of the leading causes of deaths worldwide. A number of studies confirmed the causal relationship between the development of insulin resistance (IR) and DM2. At the same time, traditionally and for many years the plants or substances isolated from them have been using in the DM2 treatment and correction of its complications. The aim of the study – to find out the effect of ethanolic polyphenol Bearberry leaves (Arctostap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
3
2
0
Order By: Relevance
“…However, NO overproduction in overweight and obese people has been attributed to augmented inducible nitric-oxide synthase (iNOS) activity in response to insulin and pro-inflammatory cytokines (9). The hypolipidemic effects of L-arginine and gingerol (35) reported in the present study agreed with previous studies for L-arginine (30,33) and gingerol. Previous studies have concluded that both factors can lower triglycerides, total cholesterol, and LDL in humans and rats.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, NO overproduction in overweight and obese people has been attributed to augmented inducible nitric-oxide synthase (iNOS) activity in response to insulin and pro-inflammatory cytokines (9). The hypolipidemic effects of L-arginine and gingerol (35) reported in the present study agreed with previous studies for L-arginine (30,33) and gingerol. Previous studies have concluded that both factors can lower triglycerides, total cholesterol, and LDL in humans and rats.…”
Section: Discussionsupporting
confidence: 91%
“…Serum testosterone levels in the L-arginine and the 6-gingerol-treated group were significantly increased compared to the HC control group, similar to other studies (32)(33)(34). Increasing testosterone levels is a fundamental goal of researchers, not only because of its effect on enhancing lipolysis and its anti-obesity effects but also because of stimulating the fertility process (32,33). The present study, in agreement with a large group of studies, showed that oral administration of L-arginine and 6gingerol significantly augmented serum testosterone levels in the study group compared to the HC group.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…At the same time, increased fasting glucose (14.2 mmol/L) and insulin (3005 pg/mL) concentrations were observed in experimental animals from HFD group. This evidence of metabolic disorders indicates the development of experimental MS in animals, which also is verified by the elevated HOMA index [ 52 ]. Extract E1 administration in dose 150 mg/kg body weight caused a significant decrease in serum glucose (down to 11.4 mmol/L), while at doses of 250 mg/kg the effect was even more significant (down to 9.1 pg/mL).…”
Section: Resultsmentioning
confidence: 89%
“…Current results are the part of the complex experiment; thus, the data proved the IR development have been already published [17]. Long-term administration of dex was accompanied by hyperglycemia and IR development.…”
Section: Resultsmentioning
confidence: 91%